Pengaruh Fraksi Berat Zirconia Terhadap Sifat Fisik dan Mekanik Komposit Matrik Alumunium Diperkuat dengan Keramik Zirconia Yang Dibuat dengan Metode Metalurgi Serbuk - , BAYU SATRIYA WARDHANA, Ir. M. Waziz Wildan, M.Sc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Aluminum is popularly material on automotive industry as its light, toughness and corrosion resistance. Nevertheless aluminum has low hardness. Itâs giving low wear resistance. To improve this condition, aluminum alloy was developed. One of improvement method is AMC (Aluminum Matrix Composites). Composite with aluminum matrix had been developing and proven to be improving mechanical properties. This research aims to utilize zirconia (ZrO2) as a reinforcement of aluminum matrix composite (AMC). ZrO2 is hard ceramic and has good high temperature resistance. ZrO2 powder of 0%, 2.5%, 5%, 7.5%, 10%, 12,5%, and 15% wt were added to fine aluminum powder (dimension of particles are smaller than 40 Î¼m). Each composition was mixed using a turbula mixer for 2 hr. The mixture was uniaxially pressed with a pressure of 300 MPa to produce green bodies. They were pressure less sintered in argon atmosphere at temperature of 600ÂºC. Relative density, Vickers hardness, wear resistance and bending strength of the AMC were tested. The results show that the hardness increases with increasing the ZrO2 content up to 5% wt whereas wear rate decrease. Relative density, Vickers hardness and wear rate of composite containing 5% ZrO2 are 89%, 34 HV15 and 0.076 mg/(MPa.m), respectively. Maximum bending strength was reach on 7,5% ZrO2 adding on 37,66 MPa.